Functional Outcome of Posterior Transpedicular Screw Fixation among Patients Presenting with Spinal Tuberculosis - Anwer, Muhammad Sohaib; Jalal, Malik Liaqat Ali; Farooq, Muhammad Shaukat; Shareef, Rizwan; Waqas, Muhammad Ali; Ali, M. (Pakistan Journal of Medical & Health Sciences, 2022)
Material and Methods; A series of descriptive case was completed at Neurosurgery Department Nishtar Hospital Multan. The time period for this study was from November 2014- September 2016. After registering the patients, under the supervision of an expert neurosurgeon results of all the clinical examinations, and medical history were recorded. The medical record reported forty-one consecutive patients were treated with one-stage posterior debridement, transpedicular fixation suffering from monosegmental lumbar spinal tuberculosis, between December 2014-August 2016, were prospectively analyzed. Results; Forty one patients were observed for this procedure 25 (61%) were male patients and 16 (39%) of the patients were female with their mean age was 29.58 years ±2 years. The average time between follow-ups was 13.6 ±2.7 months. The average pain score preoperatively was 9.2 ± 2.13 on the VAS scale and postoperatively was 2.5 ± 1.32. This decrease in back pain was statistically significant (0.05142, P > 0.05) and Complication rate was 7.31 % in these patients Conclusion; Our results support one stage posterior fixation procedure with pedicle screw in adults with lumbar spinal tuberculosis as it is safe, effective and yields desired functional outcome.